A laser shock strengthening method to improve the mechanical properties of aviation aluminum
By sandpaper pretreatment of 7050 aviation aluminum alloy, ball milling and mixing powder and applying water glass paste, combined with laser impact strengthening technology, the problem that the existing technology cannot effectively improve the mechanical properties of aviation aluminum is solved, and the effect of significantly improving tensile strength, reducing yield strength and enhancing wear resistance is achieved.
Patent Information
- Application Number
- CN202211379535.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-04
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2042-11-04
AI Technical Summary
The prior art cannot effectively improve the mechanical properties of aviation aluminum, especially in terms of tensile strength, yield strength and wear resistance, and cannot meet the high requirements for material performance in aircraft manufacturing.
The 7050 aerospace aluminum alloy was sandpapered, ball milled and mixed powder and applied to the surface, then dried in a vacuum drying box, and laser impact strengthened with a laser under argon protection.
It significantly improves the tensile strength of aviation aluminum alloy, reduces its yield strength, and significantly improves its wear resistance, meeting the high requirements for material performance in aircraft manufacturing.
Smart Images

Figure CN115627344B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aviation materials, and in particular to a laser shock strengthening method for improving the mechanical properties of aviation aluminum. Background Art
[0002] Aircraft are important means of transportation for air transportation, carrying the important mission of facilitating the flow of people and logistics. Since the working place of aircraft is at high altitude and the transportation objects are mainly people, there are high requirements for transportation quality, transportation safety, and transportation effect during the flight of the aircraft. In the process of aircraft manufacturing, the materials used need to have the characteristics of light weight, high toughness, high strength, high corrosion resistance, and high fatigue resistance. As a non-ferrous metal material composed of multiple metal elements, aviation aluminum alloy can effectively meet the basic requirements for structural material performance in the aircraft classification process to a certain extent, and has become a widely used material in aircraft structure manufacturing. Usually, in the process of aircraft structure manufacturing, aluminum alloy materials are mainly used in fuselage, supporting structure, wings and other parts. Under the support of their own performance and in cooperation with other components, they bear different loads to meet the needs of safe and stable operation of the aircraft.
[0003] Aviation duralumin 7075 is an aluminum alloy, known as the best product among aluminum alloys. This alloy has been used in the aircraft manufacturing industry since the late 1940s and is still widely used in the aviation industry. It is an ultra-high strength deformable aluminum alloy. Its characteristics are good plasticity after solution treatment, particularly good heat treatment strengthening effect, high strength below 150°C, and particularly good low-temperature strength; poor welding performance; tendency to stress corrosion cracking; and need to be clad with aluminum or other protective treatments before use.
[0004] The patent application number is CN202210708772.5, which states in its specification that "a laser shock strengthening method for improving the mechanical properties of key components of aviation bearing steel materials is provided. By laser shock strengthening treatment of fatigue damage areas of structural parts, a compressive stress layer is formed on the surface of the parts without destroying the main structure and surface state of the parts, thereby improving the fatigue limit strength of the parts. This patent takes 8Cr4Mo4V bearing steel as an example. The material is first vacuum quenched and tempered, and then the method of the present invention is used to laser shock strengthen the 8Cr4Mo4V bearing steel sample, so that a better shock strengthening layer is formed in the laser shock strengthening area. This method can form a more uniform stress distribution in the impact strengthening area on the surface of the material, and reduce the damage to the material surface caused by the destruction of the absorption protective layer, so that the impact-strengthened surface can obtain a better strengthening effect." Although the method provided by the above patent has a certain effect on strength and mechanical properties, the mechanical properties of the material after treatment are not improved, and cannot meet the use requirements.
[0005] In summary, developing a laser shock strengthening method to improve the mechanical properties of aviation aluminum is a key issue that needs to be urgently addressed in the field of aviation material technology. Summary of the invention
[0006] In view of the above-mentioned shortcomings of the prior art, the present invention provides a laser shock strengthening method for improving the mechanical properties of aviation aluminum. The method provided by the present invention can not only improve the tensile strength performance of aviation aluminum alloy and reduce its yield strength, but also improve the wear resistance of aviation aluminum alloy.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] The present invention provides a laser shock strengthening method for improving the mechanical properties of aviation aluminum, comprising the following steps:
[0009] (1) Take 7050 aviation aluminum alloy and pre-treat it with sandpaper;
[0010] (2) grinding 7050 aviation aluminum alloy powder, silicon dioxide powder and hexagonal boron nitride powder in a ball mill to obtain a mixed powder;
[0011] (3) The mixed powder is mixed with water glass into a paste, applied to the surface of 7050 aviation aluminum alloy, and dried in a vacuum drying oven;
[0012] (4) The dried 7050 aviation aluminum alloy is subjected to laser shock strengthening using a laser.
[0013] The present invention is further configured as follows: in step (1), the pretreatment process is as follows:
[0014] The surface of 7050 aviation aluminum alloy was polished with 100, 200, 400 and 800 grit sandpaper respectively;
[0015] Rinse the polished 7050 aviation aluminum alloy with alcohol for 3-4 times, and then with deionized water for 2-3 times;
[0016] The rinsed 7050 aviation aluminum alloy is dried in a drying oven to complete the pretreatment of the 7050 aviation aluminum alloy.
[0017] The present invention is further configured as follows: the temperature of the drying box is 80-90° C., and the drying time is 15-20 minutes.
[0018] The present invention is further configured as follows: in step (2), the mass ratio of the 7050 aviation aluminum alloy powder, the silicon dioxide powder and the hexagonal boron nitride powder in the mixed powder is 1:2:2.
[0019] The present invention is further configured as follows: in step (2), the rotation speed of the ball mill is 400-420 r / min, and the time is 120-150 min.
[0020] The present invention is further configured as follows: in step (3), the temperature of the vacuum drying oven is 70-72° C., and the drying time is 1-2 hours.
[0021] The present invention is further configured as follows: in step (4), the laser power of the laser shock peening is 700W, the scanning speed is 12mm / s, the spot size is 2mm, and the overlap rate is 40-42%.
[0022] The present invention is further configured as follows: in step (4), during the laser shock strengthening process, argon gas is used for protection, and the flow rate of the argon gas is 18-20 L / min.
[0023] Beneficial Effects
[0024] Compared with the known public technology, the technical solution provided by the present invention has the following beneficial effects:
[0025] The present invention grinds the surface of aviation aluminum alloy with sandpaper of 100, 200, 400 and 800 mesh respectively, then rinses with alcohol and deionized water, mixes aviation aluminum alloy powder, silicon dioxide powder, hexagonal boron nitride powder and water glass into a paste, applies it to the surface of aviation aluminum alloy, and after drying, uses a laser to perform laser shock strengthening under argon protection to improve the mechanical properties of aviation aluminum alloy; the provided method can not only improve the tensile strength performance of aviation aluminum alloy and reduce its yield strength, but also improve the wear resistance of aviation aluminum alloy, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a statistical chart of the tensile strength of aviation aluminum in the performance test 1) of the present invention;
[0027] Figure 2 It is a statistical chart of the yield strength of aviation aluminum in the performance test 1) of the present invention;
[0028] Figure 3 It is a statistical chart of the wear weight loss of aviation aluminum in the performance test 2) of the present invention. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] The present invention will be further described below in conjunction with the embodiments.
[0031] Embodiment 1:
[0032] The present invention provides a laser shock strengthening method for improving the mechanical properties of aviation aluminum, comprising the following steps:
[0033] (1) Take 7050 aviation aluminum alloy and pre-treat it with sandpaper.
[0034] Furthermore, the preprocessing process is as follows:
[0035] The surface of 7050 aviation aluminum alloy was polished with 100, 200, 400 and 800 grit sandpaper respectively;
[0036] The polished 7050 aviation aluminum alloy was rinsed with alcohol three times and then rinsed with deionized water twice;
[0037] The rinsed 7050 aviation aluminum alloy is dried in a drying oven to complete the pretreatment of the 7050 aviation aluminum alloy.
[0038] Among them, the temperature of the drying box is 80°C and the drying time is 15 minutes.
[0039] (2) 7050 aviation aluminum alloy powder, silicon dioxide powder and hexagonal boron nitride powder are ball-milled in a ball mill to obtain a mixed powder.
[0040] Furthermore, the mass ratio of 7050 aviation aluminum alloy powder, silicon dioxide powder and hexagonal boron nitride powder in the mixed powder is 1:2:2.
[0041] Furthermore, the rotation speed of the ball mill is 400 r / min, and the time is 120 min.
[0042] (3) Mix the mixed powder with water glass to form a paste, apply it on the surface of 7050 aviation aluminum alloy, and dry it in a vacuum drying oven.
[0043] Furthermore, the temperature of the vacuum drying oven is 70° C., and the drying time is 1 h.
[0044] (4) The dried 7050 aviation aluminum alloy is subjected to laser shock strengthening using a laser.
[0045] Furthermore, the laser power of the laser shock peening is 700 W, the scanning speed is 12 mm / s, the spot size is 2 mm, and the overlap rate is 40%.
[0046] Furthermore, during the laser shock peening process, argon gas was used for protection, and the flow rate of argon gas was 18 L / min.
[0047] Embodiment 2:
[0048] The present invention provides a laser shock strengthening method for improving the mechanical properties of aviation aluminum, comprising the following steps:
[0049] (1) Take 7050 aviation aluminum alloy and pre-treat it with sandpaper.
[0050] Furthermore, the preprocessing process is as follows:
[0051] The surface of 7050 aviation aluminum alloy was polished with 100, 200, 400 and 800 grit sandpaper respectively;
[0052] The polished 7050 aviation aluminum alloy was rinsed with alcohol 4 times and then with deionized water 3 times;
[0053] The rinsed 7050 aviation aluminum alloy is dried in a drying oven to complete the pretreatment of the 7050 aviation aluminum alloy.
[0054] Among them, the temperature of the drying box is 85°C and the drying time is 17 minutes.
[0055] (2) 7050 aviation aluminum alloy powder, silicon dioxide powder and hexagonal boron nitride powder are ball-milled in a ball mill to obtain a mixed powder.
[0056] Furthermore, the mass ratio of 7050 aviation aluminum alloy powder, silicon dioxide powder and hexagonal boron nitride powder in the mixed powder is 1:2:2.
[0057] Furthermore, the rotation speed of the ball mill is 410 r / min, and the time is 135 min.
[0058] (3) Mix the mixed powder with water glass to form a paste, apply it on the surface of 7050 aviation aluminum alloy, and dry it in a vacuum drying oven.
[0059] Furthermore, the temperature of the vacuum drying oven was 71° C., and the drying time was 2 h.
[0060] (4) The dried 7050 aviation aluminum alloy is subjected to laser shock strengthening using a laser.
[0061] Furthermore, the laser power of the laser shock peening was 700 W, the scanning speed was 12 mm / s, the spot size was 2 mm, and the overlap rate was 41%.
[0062] Furthermore, during the laser shock peening process, argon gas was used for protection, and the flow rate of argon gas was 19 L / min.
[0063] Embodiment 3:
[0064] The present invention provides a laser shock strengthening method for improving the mechanical properties of aviation aluminum, comprising the following steps:
[0065] (1) Take 7050 aviation aluminum alloy and pre-treat it with sandpaper.
[0066] Furthermore, the preprocessing process is as follows:
[0067] The surface of 7050 aviation aluminum alloy was polished with 100, 200, 400 and 800 grit sandpaper respectively;
[0068] The polished 7050 aviation aluminum alloy was rinsed with alcohol 4 times and then with deionized water 3 times;
[0069] The rinsed 7050 aviation aluminum alloy is dried in a drying oven to complete the pretreatment of the 7050 aviation aluminum alloy.
[0070] Among them, the temperature of the drying box is 90°C and the drying time is 20 minutes.
[0071] (2) 7050 aviation aluminum alloy powder, silicon dioxide powder and hexagonal boron nitride powder are ball-milled in a ball mill to obtain a mixed powder.
[0072] Furthermore, the mass ratio of 7050 aviation aluminum alloy powder, silicon dioxide powder and hexagonal boron nitride powder in the mixed powder is 1:2:2.
[0073] Furthermore, the rotation speed of the ball mill is 420 r / min, and the time is 150 min.
[0074] (3) Mix the mixed powder with water glass to form a paste, apply it on the surface of 7050 aviation aluminum alloy, and dry it in a vacuum drying oven.
[0075] Furthermore, the temperature of the vacuum drying oven is 72° C., and the drying time is 2 h.
[0076] (4) The dried 7050 aviation aluminum alloy is subjected to laser shock strengthening using a laser.
[0077] Furthermore, the laser power of the laser shock peening is 700 W, the scanning speed is 12 mm / s, the spot size is 2 mm, and the overlap rate is 42%.
[0078] Furthermore, during the laser shock peening process, argon gas was used for protection, and the flow rate of argon gas was 20 L / min.
[0079] Performance testing:
[0080] Aviation aluminum laser shock strengthening was performed according to the methods in Example 1, Example 2, and Example 3, and then aviation aluminum laser shock strengthening was performed using the method with patent application number CN202210708772.5, which were respectively used as Experimental Group 1, Experimental Group 2, Experimental Group 3, and Control Group.
[0081] 1) According to the testing standard of GB / T228.1-2010, the tensile strength and yield strength of each group of aviation aluminum were tested, and the data of each group of experiments were recorded in Table 1.
[0082] Table 1: Record of tensile strength and yield strength of each group of aviation aluminum
[0083]
[0084] Depend on Figure 1-2 As shown in Table 1, compared with the control group, the tensile strength of the aviation aluminum in the experimental groups (experimental group 1, experimental group 2 and experimental group 3) is stronger than that in the control group (p < 0.05), and the yield strength is lower than that in the control group (p < 0.05), while the difference in tensile strength and yield strength of aviation aluminum between experimental group 1, experimental group 2 and experimental group 3 is not obvious (p > 0.05). The method provided by the present invention can effectively improve the tensile strength of aviation aluminum and make aviation aluminum have better yield properties.
[0085] 2) According to the testing standard of GB / T12967.1-2007, the wear resistance of each group of aviation aluminum was tested (200°C), and the data of each group of experiments were recorded in Table 2.
[0086] Table 2: Record of wear resistance of each group of aviation aluminum
[0087]
[0088]
[0089] Depend on Figure 3 As shown in Table 2, compared with the control group, the wear weight loss of aviation aluminum in the experimental groups (experimental group 1, experimental group 2 and experimental group 3) was lower than that in experimental group 1 (p < 0.05), while the difference in wear weight loss between the experimental groups was not significant (p > 0.05). The method provided by the present invention can effectively improve the wear resistance of aviation aluminum.
[0090] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A laser shock strengthening method for improving the mechanical properties of aviation aluminum, characterized in that: The following steps are involved: (1) Take 7050 aviation aluminum alloy and pre-treat it with sandpaper; (2) grinding 7050 aviation aluminum alloy powder, silicon dioxide powder and hexagonal boron nitride powder in a ball mill to obtain a mixed powder; The mass ratio of 7050 aviation aluminum alloy powder, silicon dioxide powder and hexagonal boron nitride powder in the mixed powder is 1:2:2; (3) Mix the mixed powder with water glass to make a paste, apply it on the surface of 7050 aviation aluminum alloy, and dry it in a vacuum drying oven; (4) The dried 7050 aviation aluminum alloy is subjected to laser shock strengthening using a laser; The laser power of the laser shock peening is 700W, the scanning speed is 12mm / s, the spot size is 2mm, and the overlap rate is 40-42%; During the laser shock peening process, argon gas is used for protection, and the flow rate of argon gas is 18-20L / min.
2. The laser shock strengthening method for improving the mechanical properties of aviation aluminum according to claim 1, characterized in that: In step (1), the pre-processing process is as follows: The surface of 7050 aviation aluminum alloy was polished with 100, 200, 400 and 800 grit sandpaper respectively; Rinse the polished 7050 aviation aluminum alloy with alcohol for 3-4 times, and then with deionized water for 2-3 times; The rinsed 7050 aviation aluminum alloy is dried in a drying oven to complete the pretreatment of the 7050 aviation aluminum alloy.
3. The laser shock strengthening method for improving the mechanical properties of aviation aluminum according to claim 2, characterized in that: The temperature of the drying box is 80-90°C, and the drying time is 15-20 minutes.
4. The laser shock strengthening method for improving the mechanical properties of aviation aluminum according to claim 1, characterized in that: In step (2), the rotation speed of the ball mill is 400-420 r / min, and the time is 120-150 min.
5. The laser shock strengthening method for improving the mechanical properties of aviation aluminum according to claim 1, characterized in that: In step (3), the temperature of the vacuum drying oven is 70-72°C, and the drying time is 1-2 hours.
Citation Information
Patent Citations
Laser shock peening method for improving mechanical property of key component of bearing steel material for aviation
CN114959246A
Method for preparing compound coatings through laser shock induced chemical reaction
CN103726046A
Composite aluminum and aluminum alloy
JP1988247379A